PENERAPAN BUDAYA ORGANISASI PADA PT.PLN(Persero) Rayon Bangkinang - Supariyanto, Sugeng; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at PT. PLN (Persero) rayon Bangkinang with the title on the application oforganizational culture PT.PLN (Persero) Rayon Bangkinang. Knowing the purpose of this study is theapplication of organizational culture on PT. PLN (Persero) Rayon Bangkinang. And the benefits of thisresearch is to add insight and understanding of science in the field of Human Resource Management and toto increase knowledge and understanding of the culture of the organization but also for the company tobecome one of the materials evaluation of the extent to which the effectiveness of organizational culture thathas been applied by the company during this time.As a measure of this study reinforce the authors use the theory of Stephen P. Robbins (2003) on thecharacteristics of the organizational culture. Research method used is a census technique, whereby allemployees into the study sample as many as 24 employees. The results of this study indicate that theapplication of the value of organizational culture on PT. PLN (Persero) Rayon Bangkinang very strong.Key words :Organization culture, application, company